THE CHRISTOLOGY OF ST. ISAAC OF NINIVEH AND THE EAST SYRIAC THEOLOGY OF THE 7-8th CENTURIES - VESA, Benedict (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2019)
Isaac of Niniveh is one of the most prominent East Syriac author, whose dates go to a complex historical and religious time (7-8th centuries) – the Arab conquest and the West Syriac proselytism, and yet a period of flourishing theological literature. His discourses have a practical perspective and they may be easily lectured as a gnoseological-mystical itinerary, communicated in a technical language, in a line of a specific tradition(s). Theologically speaking, the possibility of achieving divine knowledge can be expressed only within the Christological frame, as Christ is the perfect Man and perfect God, and any human knowledge resides in Him. In consequence, it is dependent on the way one expresses the relation between Christ’s two natures (communicatio idiomatum). Isaac of Niniveh does not systematically deal with Christology, but one may identify in his discourses an attitude, a phraseology and a mystic theology, in consequence, described as divine knowledge, perception and vision. In this paper we will deal with Isaac’s Christological perspective in the frame of the Christological disputes of his time, and, in consequence, we will search for identifying the type of mystics he professes.